Rusia ayer, hoy y mañana : "El Imperio", de Ryszard Kapuscinski. Ed. Anagrama, Barcelona, 1997. 360 págs. - Hubeñak, Florencio (1998)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina